ANALISIS PASCA BENCANA TSUNAMI CIAMIS - CILACAP - Tejakusuma, Iwan G. (Jurnal Sains dan Teknologi Indonesia, 2008)
Earthquake with magnitude 7,7 on the Richter scale happened on 17 July 2006 in Indian Ocean, south of Ciamis District at 10 kilometer depth. The earthquake has generated tsunami and causing disaster in the coastal areas of Ciamis – Cilacap.More than 500 people died and hundred of buildings were damage. Field investigations showed that inundation along the affected coastal areas of Ciamis – Cilacap depend on the coastal morphology. In the areas with sand ridges the inundation distance were reduced significantly for example only about 150 meter in Widarapayung compared to 500 meter to 1 kilometer in Pangandaran. Damage to buldings depend on the building constructions. Wooden buildings were easily swept away by the tsunami waves. Concrete buildings without reinforced were heavily or completely damage compared to more withstand reinforced concrete buildings.